Thermal analysis of non-Newtonian fluid with radiation and MHD effects over permeable exponential stretching sheet - Nadeem Abbas; Wasfi Shatanawi; Zead Mustafa (Case Studies in Thermal Engineering)
In our recent analysis, we investigated the 3-D flow of a second-grade fluid over an exponentially stretching sheet, taking into account the variable viscosity and thermal conductivity of the fluid. We also considered the influences of a magnetic field and the characteristics of a permeable exponential stretching sheet under thermal slip condition. Furthermore, we explored the phenomena of radiation and heat generation. The governing flow system has been mathematically formulated, and boundary layer approximations are used to make simpler the differential equations. By applying appropriate transformations, we reduced the differential equations into a dimensionless (ordinary differential equations) system of equations. We then employed a numerical scheme to solve the dimensionless system, presenting the numerical results in tabular and graphical formats. Through these graphical and numerical results, we discussed the influence of several physical phenomena on the flow and examined how different parameters affected the behavior of the system. Velocity profile decreased with growing values of the magnetic field factor. As a result of the fluid encountering more flow resistance, the velocity profile become lesser. The temperature curves are seen to increase by enlarging values of heat generation.